PENERPAN METODE PERMAINAN PUZZLE DALAM PEMBELAJARAN MEMPRODUKSI TEKS CERITA FANTASI - Dasep Nuryana; Fadillah Muslim; Indra Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
The purpose of this writing is to describe a method implementation puzzle game for can produce the text of the story of fantasy, describing the use of the method of envelopes of puzzle on the text of the story of fantasy and explain difficulties in learning to write text fantasy stories using the method of games of puzzle. This research uses research methods pre-experimental design because design is not yet is circling in earnest and there are still variables that come into effect on the dependent variable. Research subject and location are learners Class VII MTS. Yamisa . The population of this research is the entire learners Class VII MTs Yamisa with a sample of learners class VIIA MTS. Yamisa that amounted to 27 students. The technique of data collection by using the techniques of tests and nontes. Test techniques in the form of writing text descriptions and nontes techniques in the form of observation. The results of the research at this stage pretes obtained average value 64, 04 while after getting treatment method using game puzzle (post-tes) obtained the value average 84, 04. Based on the results obtained showed that the method puzzle game can be used to be able to produce and regenerate the kreativitfantasy story writing text us on in class VII.